PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING SUBMATERI JANTUNG DAN PROSES PEREDARAN DARAH MANUSIA DI SMA - Mirawati, Isra; Ningsih, Kurnia; Panjaitan, Ruqiah Ganda Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study is aimed to develop Student Worksheet based on discovery learning on the sub-lesson about heart and human circulatory process, as well as to discover studentsâ€™ responses to the product developed. Research and Development (R&D) conducted consists of 7 stages: research and data collection, planning, product draft development, limited product testing, revision, main field test, and revision to the operational product. The product was approved by 2 validators to measure the feasibility by evaluating the contents, language, course, and graphic aspects. The test was done to determine the studentsâ€™ responses in the cognitive, affective, and conative aspects. The subjects in this study are the 11th-grade Mathematics and Natural Sciences students of SMAN 7 Pontianak, MAN 1 Pontianak, and SMA Mujahidin Pontianak. The validation of each aspect showed a value of 1.00, categorized as very high. Limited trials showed that the averages of cognitive, affective, and conative dimensions were respectively 83.33%, 80.86%, and 84.44%, as well as the main field test averaged respectively 83,71%, 81,17%, and 84,16%. Therefore, the Student Worksheet based on discovery learning is feasible to be used as the teaching material. With very strong responses, determined that the response given by the learners is highly positive.Â Keywords: Discovery Learning, Heart and Human Circulatory Process, Response, Student Worksheet.